Blended instruction for EFL learners: Engagement, learning and course satisfaction - Kızıl, Aysel Şahin (My University, 2014)
Offering blended courses has increasingly become common at tertiary education though it is relatively new in the field of language teaching. This paper describes the design of a blended language course through Moodle in an efl context with an emphasis on students’ perceptions. In a survey based approach, a total of 68 university students’ experiences with blended language learning for two consecutive terms were examined. The questionnaire items focused on the effect of blended design on students’ engagement, learning and overall course satisfaction. Student responses revealed that technology-assisted language instruction provided in parallel with face to face teaching could create efficient learning environments.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Blended language learning; Course management system; Moodle